Distribution of goods and international jurisdiction / La concesión de venta y la competencia judicial internacional - María Asunción Cebrián Salvat (Barataria, 2015)
The characterization of the different kinds of distribution contracts under art. 5.1 Brussels I Regulation (current art. 7.1 Brussels I Regulation Recast) is a controversial issue. This paper analyzes the different doctrinal and jurisprudential positions in relation to this subject and defends the opinion of the European Court of Justice regarding these contracts, this is, that they should be considered as a provision of services delivered by the distributor.